Information security theory and practice : 11th IFIP WG 11.2 International Conference, WISTP 2017, Heraklion, Crete, Greece, September 28-29, 2017, Proceedings /: 11th IFIP WG 11.2 International Conference, WISTP 2017, Heraklion, Crete, Greece, September 28-29, 2017, Proceedings. (2018) - Unknown
No abstract available